2011
DOI: 10.1515/zna-2011-1-205
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic Flow in a Deformable Channel

Abstract: Optofluidics is increasingly gaining impact in a number of different fields of research, namely biology and medicine, environmental monitoring and green energy. However, the market for optofluidic products is still in the early development phase. In this manuscript, we discuss modular platforms as a potential concept to facilitate the transfer of optofluidic sensing systems to an industrial implementation. We present microfluidic and optical networks as a basis for the interconnection of optofluidic sensor mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…On the other hand, the villous protrusion structure on the inner walls of the SIMR was also advantageous to prevent the formation of the fouling in the SIMR, as the motion of the villous protrusions under the peristaltic action can cause the local disturbance of the fluid in the SIMR, which the mean residence time of the particulates (Deng et al 2014). Furthermore, the simulated peristalsis on the SIMR could increase the mean flow rate of fluid when the peristaltic frequency increased (Misra and Pandey 1994;Marawat et al 2011, so it helped the CaCO 3 particulates be carried out of the SIMR by the fluid. It was reported that the suspension was redistributed by the reverse flow and vorticial flow induced by peristalsis (Jeffrey et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the villous protrusion structure on the inner walls of the SIMR was also advantageous to prevent the formation of the fouling in the SIMR, as the motion of the villous protrusions under the peristaltic action can cause the local disturbance of the fluid in the SIMR, which the mean residence time of the particulates (Deng et al 2014). Furthermore, the simulated peristalsis on the SIMR could increase the mean flow rate of fluid when the peristaltic frequency increased (Misra and Pandey 1994;Marawat et al 2011, so it helped the CaCO 3 particulates be carried out of the SIMR by the fluid. It was reported that the suspension was redistributed by the reverse flow and vorticial flow induced by peristalsis (Jeffrey et al 2003).…”
Section: Resultsmentioning
confidence: 99%